PROJECT-ORIENTED SELF-ORGANIZED LEARNING ENVIRONMENT (SOLE-PROJECT MODEL) AS AN EFFORT TO ENHANCE HIGH ORDER THINKING SKILLS (HOTS) OF HIGH SCHOOL STUDENTS - Abu, St. Hayatun Nur; Rahman, Nurul Aulia; Gustina, Gustina; Hamsyah, Eka Fitriana (Jurnal IPA Terpadu, 2024)
This study aims to determine the effectiveness of Self Organized Learning Environment (SOLE) oriented project (SOLE- Project Model) in improving students' HOTS. The type of research is pre-experimental design with a research design of one-group pretest-posttest. The population in this study was all students of class XI IPA 4 of SMA Negeri 2 Bone and the sampling technique was simple purposive technique. The data collected is in the form of students' HOTS ability test results. The test used is in the form of essay questions to measure students' HOTS. HOTS indicators that are assessed are the ability to analyze, evaluate, create, think critically and solve problems. The results of the study based on the Paired sample T test obtained sig is 0.000, it can be concluded that the SOLE-Project learning model is effective to improve students' HOTS. Students who are trained to think using HOTS will have a positive impact on their educational development.